Consequences of risk factors related to prolonged computer use on musculaokeletal pain in public unversity students: A case study - Fazilah, Abdul Aziz; Nur Aisyah Mardhiah, Halim (Penerbit UMP, 2022)
The Malaysian government formally enforces study, worship, and online learning rules during the movement control order period. Learning activities that used to be carried out face-to-face have now been changed mainly into virtual meetings. These conditions affect the effectiveness of the student's well-being and learning process in higher education. This study aims to determine the problems and risk factors of continuous computer use on a person's musculoskeletal system. This cross-sectional study was conducted on 60 volunteers from a public university student body in Pahang. Data were collected using a structured socio-demographic, work-related factors questionnaire and the Nordic Musculoskeletal Questionnaire (NMQ) for MSD assessment. Each student's severity of MSD symptoms was assessed by a visual analogue scale (VAS). Robust Poisson regression was used to investigate the association of MSDs with socio-demographic and other study-related factors. More than 60% of students experienced symptoms of musculoskeletal problems in the neck, shoulder, upper back, and lower back. This study found that gender and not taking a break from electronic devices lead to musculoskeletal discomfort among students. In addition, this result shows that revision activity leads to musculoskeletal discomfort in the neck and low back among students. Moreover, class attendance led to musculoskeletal discomfort in the lower back. These findings provide awareness regarding musculoskeletal discomfort risk factors among students in university institutions.